2020
DOI: 10.3389/fphar.2020.00810
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Susceptibility-Related Factors and Biomarkers of Xianling Gubao Capsule-Induced Liver Injury

Abstract: Although increasing reports from the literature on herbal-related hepatotoxicity, the identification of susceptibility-related factors and biomarkers remains challenging due to idiosyncratic drug-induced liver injury (IDILI). As a well-known Chinese medicine prescription, Xianling Gubao Capsule (XLGB) has attracted great attention due to reports of potential liver toxicity. But the mechanism behind it is difficult to determine. In this paper, we found that XLGB-induced liver injury belongs to IDILI through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Therefore, CFDA has also warned of the risks of liver damage from XLGB in 2016 and turned this drug from over-the-counter treatment to prescription. Furthermore, when lipopolysaccharide (LPS) and XLGB were co-administrated to OVX rats, marked hepatotoxicity was observed ( Wu et al, 2019 ; Li et al, 2020 ). Also, mild immune stress, disrupted lipid metabolism, extensive liver necrosis and inflammatory infiltration, apoptosis, and expression of oxidative stress-related proteins may be associated with XLGB-induced hepatotoxicity in humans ( Wu et al, 2019 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CFDA has also warned of the risks of liver damage from XLGB in 2016 and turned this drug from over-the-counter treatment to prescription. Furthermore, when lipopolysaccharide (LPS) and XLGB were co-administrated to OVX rats, marked hepatotoxicity was observed ( Wu et al, 2019 ; Li et al, 2020 ). Also, mild immune stress, disrupted lipid metabolism, extensive liver necrosis and inflammatory infiltration, apoptosis, and expression of oxidative stress-related proteins may be associated with XLGB-induced hepatotoxicity in humans ( Wu et al, 2019 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when lipopolysaccharide (LPS) and XLGB were co-administrated to OVX rats, marked hepatotoxicity was observed ( Wu et al, 2019 ; Li et al, 2020 ). Also, mild immune stress, disrupted lipid metabolism, extensive liver necrosis and inflammatory infiltration, apoptosis, and expression of oxidative stress-related proteins may be associated with XLGB-induced hepatotoxicity in humans ( Wu et al, 2019 ; Li et al, 2020 ). Meanwhile, eight endogenous components including sphinganine, glycerophosphoethanolamine, and phenylalanine were identified as the potential biomarkers for XLGB-induced liver injury ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum phenylalanine levels related to immune activation were detectable in patients with Alzheimer’s disease, in the pathogenesis of which immune activation and inflammation represented critical mechanisms ( Wissmann et al, 2013 ). Li et al suggested that mild immune stress caused metabolic reprogramming including phenylalanine metabolism ( Li C.Y. et al, 2020 ), implicating a potential relationship between immunomodulation and phenylalanine related metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In fecal metabolomics, the level of phenylalanine increased after low-dose administration both on day 10 and day 21. Phenylalanine was identified as a potential biomarker of drug-induced hepatotoxicity with metabolomics analysis (Li et al, 2020a ; Tu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%